Development of high-throughput imaging mass spectrometry - Burleigh, R (2019)
Mass specific surface images with micron and sub-micron spatial resolution can be recorded with a mass spectrometer. Ion microscope mass spectrometry imaging uses a defocused laser or ion beam to simultaneously analyse large sample areas. The ions are subsequently separated by their time-of-flight (ToF) and their spatial location is electrostatically transferred onto a two-dimensional position-sensitive detector. The detected ions are converted to light and recorded by either, a charged coupled device (CCD) camera and a photo multiplier tube (PMT), or an event-triggered complementary metal-oxide semiconductor (CMOS) sensor. CMOS sensors such as the Timepix3 cam and a PImMS camera are capable of multi-mass ion imaging. The result is a series of images corresponding to each recorded m/z, further demonstrating the high-throughput capability of the instrument. An ion microscope has three drawbacks when compared to microprobe MSI: low mass resolution, a small mass range and poor spatial resolution. For each of these limitations, this thesis presents a solution that can be applied simultaneously to improve the performance and applicability. An ion microscope, incorporating a reflectron, was used to simultaneously image mass-resolved ions generated from a 0.3mm diameter surface. Mass and spatial resolutions of 8100±700m/Δm and 14 μm were obtained by using post extraction differential acceleration (PEDA) ion optical focusing to create a pseudo-source plane for a single-stage gridless reflectron. The obtainable mass resolution was limited only by the response time of the position-sensitive detector, and could potentially reach 30 200±2900m/Δm. Single-field PEDA has a mass-resolved window that is approximately 19% of the spatially-resolved mass window. A time-dependent pulse applied after ions have exited the extraction region facilitates an increase in the mass resolution over the entire spatially resolved mass range. The potential energy surface of the time-dependent pulse is chosen so that it approximates the dependency between the ion ToF and molecular weight. Mass resolution between 2500 - 8100m/Δm has been achieved for ions between 300 - 625 Da, whilst preserving approximately 14 μm spatial resolution. The spatial resolution has been improved in silico with the introduction of a four-plate ion optic. The electrode arrangement and potentials have been optimised using minimisation routines. An 800 nm spatial resolution has been achieved with the optimised ion optics. The Timepix3 cam has recorded time resolved ion images from a reflectron ion microscope. The camera has been operated in continuous readout mode and the individual experiments have been separated using optical fibre that directs part of the laser pulse onto the sensor. This provides an alternative to the expensive readout systems that are typically used. The resolutions achieved with this technique are comparable to those obtained using a CCD/PMT combination.